Revitalization Model The Role of Tigo Tungku Sajarangan in Fostering Character of Children in Minangkabau Family and Its Socialization Through Website - Sitompul, Roswita; Alesyanti, A; Hartono, H; Saleh Ahmar, Ansari (International Journal of Engineering and Technology, 2018)
Globalization is not a process of depriving identity, but a process for maintaining the identity of a nation. Maintenance does not mean to close themselves from the influence of foreign culture. The values contained within a culture must have the ability to adapt and adapt to other cultures through a selection process. Considering the social phenomenon that is happening in the daily life of Minangkabau society, implied the roots of cultural values, especially the value of characters, began to erode in the education of children in the family. The value of the character is almost no longer reflected in the daily life of Minangkabau youth. In fact there is an extreme statement that is often expressed by adat leaders, that at the level of the concept of Minangkabau human still densely, but not in line with the level of behavior. Changes in behavior of the younger generation seems to have tercerabut from the roots of culture.Starting from the above phenomenon, the researcher wanted to re-question the tasks and functions of the tuahku sajar tungku, which had been instrumental in providing character values for the children and nephew in Minangkabau, but slowly the task began to shift and rely on the parents alone. The question that arises here is why customary law no longer raises the responsibility of planting the value of character to the tuah kuung sangan, what factors lead to waning the spirit of character values in the education of children in the family, and how the model design that can be used as a reference for the effort to re-revitalize the role of tigo stoves in helping parents in instilling character values on Minangkabau family. This model is expected to be known to many people through socialization by using the website.Â Â